Irish soda bread murder - O'Connor, Carlene; Ehrhart, Peggy; Ireland, Liz (Kensington Cozies, 2025)
Irish Soda Bread murder by Carlene O'Connor: There's very little time left before her wedding, but nonetheless Tara Meehan is helping out at her Uncle Johnny's salvage yard for the day. Aunt Rose set up a convention for local psychics, including a bake sale to raise money for charity, but now she's sick and available only via an iPad Johnny is carrying. The event promises to deliver a real pot of gold until Rose's biggest rival shows up. Before Tara can utter a simple "top o' the morning" to the man, he drops dead--with Johnny's soda bread in his hands. It's up to Tara to identify the deadly baker before another victim ends up chasing the rainbow straight into a grave . . .